1995
DOI: 10.1016/0014-5793(95)00909-s
|View full text |Cite
|
Sign up to set email alerts
|

The MIG1 repressor from Kluyveromyces lactis: cloning, sequencing and functional analysis in Saccharomyces cerevisiae

Abstract: Sequence comparisons between [9,10]. Moreover, in addition to its galactokinase activity, the K. lactis GALl gene product has a regulatory function required for the induction pathway, upstream of K1LAC9 [11]. Interestingly, a potential MIGl-binding site is found in the GALl promoter of K. lactis suggesting the involvement of a Migl-like protein in glucose repression of galactose-lactose catabolism in K. lactis.The SUC2 gene encoding invertase in S. cerevisiae, on the other hand, displays two MIG 1-binding site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 29 publications
4
42
0
Order By: Relevance
“…However, it lacks the PXXP core motif, which is thought to be crucial for SH3 binding (27). The proline-rich motif is conserved in Mig1 from K. lactis (5), which is consistent with the notion that it plays an important role in vivo. Similar motifs are also found in the more distantly related Mig1 homolog CREA (7) and in the Rox1 repressor (2).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, it lacks the PXXP core motif, which is thought to be crucial for SH3 binding (27). The proline-rich motif is conserved in Mig1 from K. lactis (5), which is consistent with the notion that it plays an important role in vivo. Similar motifs are also found in the more distantly related Mig1 homolog CREA (7) and in the Rox1 repressor (2).…”
Section: Discussionsupporting
confidence: 76%
“…Significantly, the C-terminal part of the effector domain including the leucine-proline repeats and the RSL motif is conserved in Mig1 from Kluyveromyces lactis (5), which suggests that these residues are functionally important ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…The respective situation has been much less explored in glucose-repressible strains of K. lactis; however, the existence of an ScMig1 homolog (KlMig1) has been inferred from homology considerations, and complementation of a mig1 mutant of S. cerevisiae by the homologous K. lactis gene has shown that the function of Mig1 is conserved in these distantly related yeasts (64). Keeping in mind both the considerable degree of sequence identity between KlHxk1 and ScHxk2 (73%) (22), with a striking conservation of amino acids in the intersubunit interface including the in vivo phosphorylation site, Ser-15, and the comparably high degree of identity (70.6% in an 85-residues overlap) in the N-terminal part of the KlMig1 and ScMig1 proteins, a mechanism of Mig1-hexokinase interaction similar to that proposed for S. cerevisiae may also be anticipated for K. lactis.…”
Section: Discussionmentioning
confidence: 99%
“…Two smaller deletions define the domain further: deletion of amino acids 174-391 also results in a partially constitutive repressor ( Table 4, pBM3255) that is constitutively in the nucleus ( Figure 6A, parts 3 and 4); deletion of amino acids 97-173 has little effect on glucose regulation of transcriptional repression (Table 4, pBM3350) and no apparent effect on regulation of nuclear localization ( Figure 6A, parts 5 and 6). This region of the protein contains two stretches very rich in the basic amino acids characteristic of nuclear localization signals, one of which is conserved in the Migl homologs of Kluyveromyces lactis and Kluyveromyces marxianus and is very similar to the well-characterized nuclear localization signal of the yeast transcription factor Swi5 (Cassart et al, 1995;Ostling et al, 1996). However, these sequences are not required for the nuclear localization of Migl ( Figure 6A, parts 5 and 6) and thus are unlikely to be involved in nuclear localization.…”
Section: Nuclear Localization Of Migl Is Regulated By Glucosementioning
confidence: 99%